TỔNG HỢP CLAY POLYPYROL VÀ ỨNG DỤNG NHƯ CHẤT ỨC CHẾ ĂN MÒN CHO LỚP PHỦ EPOXY TRÊN NỀN THÉP CACBON - Trúc, Trịnh Anh; Xuân Hằng, Tô Thị (Vietnam Journal of Chemistry, 2012)
In this paper, clay polypyrrole and clay polypyrrole doped by vanadate were prepared by chemical synthesis. X-Ray diffraction analyze shows that polypyrrole was insert into clay layers and the increase of basal spacing of clay is 0.1 nm for clay polypyrrole and 0.43 nm for clay polypyrrole doped by vanadate. Clay polypyrrole was incorporated into epoxy resin for protection anticorrosion of carbon steel. The electrochemical impedance measurements show a significantly improvement of protective properties in presence of clay polypyrrole doped by vanadate in comparison with pure epoxy, epoxy containing clay and epoxy containing clay polypyrrole. The fracture surface of epoxy resin loaded was observed by FESEM. The results show a toughness improvement of epoxy resin containing polypyrrole doped vanadate.